2007
DOI: 10.1152/ajpregu.00511.2007
|View full text |Cite
|
Sign up to set email alerts
|

Load-dependent effects of duodenal lipid on antropyloroduodenal motility, plasma CCK and PYY, and energy intake in healthy men

Abstract: Both load and duration of small intestinal lipid infusion affect antropyloroduodenal motility and CCK and peptide YY (PYY) release at loads comparable to and higher than the normal gastric emptying rate. We determined 1) the effects of intraduodenal lipid loads well below the mean rate of gastric emptying on, and 2) the relationships between antropyloroduodenal motility, CCK, PYY, appetite, and energy intake. Sixteen healthy males were studied on four occasions in double-blind, randomized fashion. Antropylorod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
67
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 43 publications
4
67
0
Order By: Relevance
“…With respect to the Effect of ileal fat infusion on satiety PWJ Maljaars et al duodenum, a relation between fat load and satiating effect has been demonstrated previously. 24 It is not apparent why no dose-dependent effects of ileal fat on satiety were observed. Several factors may be involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the Effect of ileal fat infusion on satiety PWJ Maljaars et al duodenum, a relation between fat load and satiating effect has been demonstrated previously. 24 It is not apparent why no dose-dependent effects of ileal fat on satiety were observed. Several factors may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pilichiewicz et al 24 demonstrated that, after duodenal infusion of lipid, a threshold infusion rate exists for fat to be able to induce PYY release. They demonstrated that a load of 0.25 kcal min À1 did not increase PYY plasma levels, whereas 1.5 kcal min À1 did.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of the magnitude of the effects of L-Phe on APD motility and CCK secretion with the effects seen in response to ID protein, glucose, fat or free fatty acids in our previous studies with similar experimental designs reveals that the APD and CCK responses to L-Phe are rather small. 3,[37][38][39] However, it needs to be recognised that while free fatty acids were administered at comparable loads of 0.4 kcal/min, 39 protein, carbohydrate and fat were administered in much higher caloric loads of up to 4 kcal/min. 3,37,38 We have recently identified an important role of phasic pyloric pressures and plasma CCK as independent determinants of energy intake in response to ID lipid and carbohydrate infusions.…”
Section: Discussionmentioning
confidence: 99%
“…3,[37][38][39] However, it needs to be recognised that while free fatty acids were administered at comparable loads of 0.4 kcal/min, 39 protein, carbohydrate and fat were administered in much higher caloric loads of up to 4 kcal/min. 3,37,38 We have recently identified an important role of phasic pyloric pressures and plasma CCK as independent determinants of energy intake in response to ID lipid and carbohydrate infusions. 40 Although we do not relate the present data to effects on ad libitum eating, our findings contribute to a better understanding of the mechanisms underpinning the pronounced satiating capacity of high-protein diets.…”
Section: Discussionmentioning
confidence: 99%